STATE SOVEREIGNTY, INTERNATIONAL HUMAN MOBILITY AND HUMAN RIGHTS - Vedovato, Luís Renato; Naspolini, Samyra Haydêe Dal Farra (Revista de Direito Brasileira, 2015)
International human mobility and human rights can be linked by the dinamogenesis theory. The State sovereignty isn’t the same it was in the past. The State can’t decide about the right to entry without consider international human rights treaties. The nationality has an important row in finding how dinamogenesis can modify the interpretation of the State sovereignty. The right to entry is built in the evolution of human rights. Now State has no more the discretion to decide who can enter its territory, due to dinamogenesis and human rights.